Factors Contributing to the Maintenance of Konjo Language in Heterogeneous Area of Bulukumba Regency (in the Perspective of Ethnolinguistic Vitality) - Ningsih, Sri (Ethical Lingua: Journal of Language Teaching and Literature, 2016)
The use of an ethnic language depends on the strength of the language and the efforts of the community to maintain its language. The study aims to describe the factors contributing to the survival of the language viewed from ethno-linguistic vitality and its vitality degree. The study was carried out in Ujung Bulu as the city of Bulukumba regency which is inhabited by various ethnic people (heterogeneous region). It is a descriptive quantitative-qualitative study applying observation, questionnaire distribution, and interview to collect data from a sample of 30 subjects selected based on age groups by means of multi-stage sampling technique. The study indicates that in the heterogeneous area proves that demography factors have insignificant contribution to the maintenance of Konjo language in the regency as indicated by regression value of demography factors p = 0.741. The statuses and institutional factors however have a significant contribution to the maintenance of the language with the values of p = 0.010 and p = 0.002 respectively. Based on the quantitative data analysis and interview as well as observation, the vitality of Konjo language in Bulukumba regency is high as indicated by the use of the language.